Perfil do traumatismo cranioencefálico e sua associação prognóstica com a dosagem sérica de creatinina à admissão - CORREIA, Murillo Martins (2019)
INTRODUCTION: Traumatic brain injuryi (TBI), is a complex event, loaded with population and regional peculiarities, with multiple causes and different levels of severity, possessing a varied range of prognostics. OBJECTIVES: To characterize the profile of the victims of TBI in the Triângulo Mineiro Sul and to identify a prognostic association of serum creatinine dosage at admission. METHODS: This is a quantitative, retrospective study based on the analysis of data from medical records of patients who were victims of TBI attended at the General Hospital of the Federal University of Triângulo Mineiro (HC-UFTM) in the city of Uberaba, Minas Gerais, in the period of January From 2007 to December 2017. RESULTS: Included 1347 patients. Predominated males (82.1%), the age group of young adults (29.7%) and main etiology of traffic accidents (57.2%) with emphasis on motorcyclists (21.9%). Tomographic alteration was evidenced in 78.1% of the sample and mortality was 17.3%. In the elderly, falls (47.3%) prevailed, with emphasis on falls from their own height (26.6%) as the main etiology. The death outcome showed significant association with: male gender (OR: 1.73; CI: 1.14-2,64), age group of the elderly (RC: 2.35; IC: 1,66-3,34) and adults (OR: 1.99; CI: 1,47-2,71), moderate TBI (OR: 3.31; CI: 1.95-5,60) and severe TBI (OR: 12,78; CI: 8,76-18,64), gunshot wounds (OR: 4.10; CI: 2.13-7,89), presence of tomographic alteration (OR: 5.28; CI: 3,02- 9,21), cerebral contusion (OR: 1.44; CI: 1.07-1,93), subdural hematoma (SH) (OC: 3,89; CI: 2.83-5,34), hemoventriculus (OR: 3,29; CI: 1.46-7,41), traumatic subaranoid hemorrhage (TSH) (OR: 1.42; CI: 1.02-1.96), cerebral swelling (OR: 5.49; CI: 3,86- 7,81), neurosurgery (OR: 2.23; CI: 1,64-3,05), chest trauma (OR: 2,79; CI: 1,74-4,45) and abdômen trauma (OR: 2.10; CI: 1.11-3.95). The mean serum creatinine value was higher in males, severe TBI, altered tomographic, SH, cerebral swelling, pneumoencephalon, death outcome, and increased values the higher the age group. Serum creatinine was also independently associated with the outcome of death (after adjustment by multivariate logistic regression) (OR: 1.64; CI: 1.25 – 2.15). The serum creatinine value of 1.18 mg/dL represented the cutoff point for better specificity (89.12%; CI: 86,4-91,5) and sensitivity (42.13%; CI: 34.8-49,7). CONCLUSION: Epidemiological information and associations that have not been reported in brazilian retrospective studies have been approached. In addition to presenting serum creatinine as a promising laboratorial predictor of TBI.